Post-operative pain management with non-pharmacological interventions in patients undergoing breast cancer surgery: A systematic scoping review - Hikmat, Rohman; Rahayu, Urip; Pebrianti, Sandra; Cahyani, Eka Maulidya; Sari, Cindy Puspita; Afrilia, Ghea (The Journal of Palembang Nursing Studies, 2022)
Background: Breast cancer become the most incident of cancer among women, especially in Indonesia. Non-pharmacological therapy becomes the additional intervention to address the pain after breast cancer surgery. Objective: The purpose of this study was to determine various non-pharmacological therapeutic interventions that can be performed in pain management in post-operative breast cancer patients. Design: The design used in this literature review is a systematic scoping review. Data Sources: This study used a scoping review system where after obtaining articles from three databases there are CINAHL, Pubmed, and Proquest. Review Methods: The articles will be synthesized and assessed using the clinical appraisal tools of Joanna Briggs Institute (JBI). JBI version of Randomized controlled trial. Results: From the total of 577 articles searched in the database, we obtained seven articles included in the study. The interventions to reduce pain include music therapy and progressive muscle relaxation therapy, acupuncture, foot reflexology, massage and meditation, autology, mindfulness-based cognitive therapy (MBCT), and neuromuscular taping on musculoskeletal (NMT). Apart from relieving pain various interventions that can be done can improve well-being, reduce stress, and reduce the length of treatment or treatment. Conclusions: The result of this study can be an additional intervention that can be applied by nurses and other health care workers.